2017
DOI: 10.1039/c7cc01750b
|View full text |Cite
|
Sign up to set email alerts
|

Rationalizing the relative abundances of trimetallic nitride template-based endohedral metallofullerenes from aromaticity measures

Abstract: The synthesis of endohedral metallofullerenes (EMFs) from a carbon soot sample leads to a variety of EMFs that are obtained in different relative abundances. In this work, we show that these abundances can be predicted from aromaticity calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Following the line started with our previous study, we generalized the ALA index to expand its scope [32]. In this work, we proposed the normalization of the ALA index per number of rings present in the fullerene structure to allow the comparison between fullerenes with different number of carbon atoms, as follows:…”
Section: Understanding the Relative Abundances Of Tnt-based Endohedramentioning
confidence: 99%
See 2 more Smart Citations
“…Following the line started with our previous study, we generalized the ALA index to expand its scope [32]. In this work, we proposed the normalization of the ALA index per number of rings present in the fullerene structure to allow the comparison between fullerenes with different number of carbon atoms, as follows:…”
Section: Understanding the Relative Abundances Of Tnt-based Endohedramentioning
confidence: 99%
“…As we will show in this review, aromaticity plays also a key role in determining the most stable isomer for the EMF encapsulation [31]. Aromaticity can also be used to rationalize the experimental EMF abundances obtained in the laboratory [32].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is indicated that the structures of fullerene isomers also play a significant role in the electron-transfer character of inner moieties. Moreover, Garcia-Borras and co-workers have pointed out that cage aromaticity is the most important stabilizing factor in the process of EMF formation. , In fact, except for U@C 74 and U@C 82 series, mono-EMFs U@C 70 and U@C 72 were detected in experiments dating back to 1992 by Smalley and co-workers . The structures of U@C 70 and U@C 72 were only characterized by FT-ICR mass spectral analysis but without any detailed structural characterization.…”
Section: Introductionmentioning
confidence: 99%
“…Garcia‐Borràs et al have suggested that the maximum aromaticity criteria correlates with the most suitable host carbon cage for a given metallic cluster in endohedral fullerenes . The same group, computed aromaticity using a number of different codes and showed that the normalized additive local aromaticity index can be used to explain the relative abundance of the trimetallic endohedral fullerenes …”
Section: Introductionmentioning
confidence: 99%